Using partial least squares regression as a predictive tool in describing equine third metacarpal bone shape. Issue 15 (18th November 2017) - Liley, Helen; Zhang, Ju; Firth, Elwyn; Fernandez, Justin; Besier, Thor
Abstract: Population variance in bone shape is an important consideration when applying the results of subject-specific computational models to a population. In this letter, we demonstrate the ability of partial least squares regression to provide an improved shape prediction of the equine third metacarpal epiphysis, using two easily obtained measurements.